Using cDNA-AFLP and microarray analysis for rapid identification of Diuraphis noxia induced genes from near-isogenic Triticum aestivum lines - Oberholster, A.M. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.